TASAVVUFTA AHLAK EĞİTİMİ (KÛTU'L KULÛB ÖRNEĞİ) - KAYA, TÜBA (Fırat Üniveristesi, 2023)
Köklü bir geçmişi olan tasavvuf insanın eğitilmesini gaye edinen bir müessesedir. Bireyler tasavvufi eğitim ile kendilerinde bulunan insani vasıflarını ortaya çıkarmaya çalışmaktadırlar. Uygulamalı eğitime ağırlık veren tasavvufi eğitim sürecinde; sohbet, tefekkür, hizmet, halvet gibi çok çeşitli eğitim metotları kullanılmaktadır. Tasavvufi eğitim insanın manevi gelişimini gaye edinerek onu ahlaki olgunluk seviyesine ulaştırmayı hedefleyen bir sistemdir. Ahlaki olarak insanı terbiye edip, güzel vasıflarının kalıcı olması için tasavvufun kurumları olan tekkelerde ahlak eğitimini sürdürmüşlerdir. Zira tasavvufi eğitimi diğer eğitim sistemlerinden ayıran en belirgin faktör bireysel ve toplumsal eğitimin beraber uygulanmasıdır. Çalışmanın temel amacı kötü ahlakın çok fazla arttığı çağımızda, Kûtu'l Kulûb'u temel alarak kişiyi kötü davranışlardan uzaklaştırıp, ahlakını güzelleştirip, onu terbiye etme yollarına yönlendirmektir. Mekki'nin Kûtu'l Kulûb'da bahsettiği ahlakı düzeltme yolları ve yöntemleri de bu hedef istikametinde içerik analizi yöntemiyle incelenmiştir. Bu teknik ile eserde Mekki'nin ahlak eğitimi ile ilgili düşüncelerine ulaşılmıştır. Tasavvufi eğitimin temel kavramları olan tövbe, sabır, şükür, havf, reca, zühd vb. birçok kavram Mekki'nin ahlak eğitimi hususundaki fikirleri irdelenerek konunun çatısı oluşturulmaya çalışılmıştır. Kûtu'l Kulûb incelendiğinde; Mekki insanın kişisel özelliklerinin ve psikososyal gelişimlerinin üzerinde durarak ahlakın terbiye edilebileceğini ifade etmektedir. Bununla ilgili en önemli görev insanın kendisine düşmektedir. Zira ahlakın terbiye edilmesinde öğrenilen ilmin uygulamaya geçirilerek sürekliliği sağlanmalıdır. Bu bağlamda sürekliliğin devam edebilmesi adına insanın nefsin arzu ve istekleri ile mücadele etmesi hal ve hareketlerinde dengeyi sağlaması esastır. Kûtu'l Kulûb örneğinde görüldüğü gibi sosyal hayatta özellikle ahlak eğitiminde son derece önemli bir vazife üstlenen tasavvufi eğitimde deneyim ve uygulamaların çok önemli bir yönü bulunmaktadır. Bundan dolayı tasavvufi eğitim ahlak eğitiminin tüm yönlerine fayda sağlayabilecek niteliktedir.

Sufism, with its deep-rooted history, is an institution that aims to educate individuals. Through Sufi education, individuals strive to manifest their inherent human qualities. The Sufi education process, which emphasizes practical training, utilizes various educational methods such as discourse, contemplation, service, and seclusion. Sufi education is a system that seeks to elevate individuals to a level of moral maturity by adopting spiritual development as its goal. In order to cultivate individuals morally and ensure the longevity of their virtuous qualities, moral education has been perpetuated within the institutions of Sufism, known as tekkes. What distinguishes Sufi education from other educational systems is the simultaneous implementation of individual and societal education. The main objective of this study is to address the proliferation of unethical behavior in our contemporary age by taking Kûtu'l Kulûb as a basis and directing individuals towards ways of distancing themselves from such behavior, refining their morality, and providing them with guidance for personal development. The paths and methods of moral rectification mentioned by Mekki in Kûtu'l Kulûb were examined through content analysis in line with this objective. This technique allowed for accessing Mekki's thoughts on moral education in the work. The fundamental concepts of Sufi education, such as repentance, patience, gratitude, fear, hope, asceticism, and others, were explored to establish the framework of Mekki's ideas on moral education. Upon examination of Kûtu'l Kulûb, it is evident that Mekki emphasizes the personal characteristics and psychosocial development of individuals, asserting that morality can be nurtured. The most significant responsibility in this regard lies with the individual themselves. The continuity of moral education relies on the practical implementation of acquired knowledge. Therefore, in order to maintain continuity, individuals must strive against their own desires and inclinations, and strike a balance in their thoughts and actions. As demonstrated by the example of Kûtu'l Kulûb, Sufi education plays a crucial role, particularly in moral education in social life, with its significant focus on experience and practice. Consequently, Sufi education possesses qualities that can benefit all aspects of moral education.
Moral education in sufism: A case study of Kûtu'l Kulûb
Keywords: Din